Strategic Decision Analysis for Electric Dump Truck Adoption in Hauling Projects: A Benefit-Cost and Return Evaluation at PT Borneo Indobara - Wahyudi; Pri Hermawan (Jurnal Syntax Transformation, 2025)
PT Borneo Indobara (BIB), a coal mining company in Indonesia, faces escalating operational costs due to diesel fuel dependency and volatile prices, exacerbated by impending subsidy reductions. Transitioning to electric dump trucks (DT EVs) presents a potential solution, but requires rigorous feasibility analysis. This study evaluates DT EV adoption against hybrid and internal combustion alternatives, aiming to identify the most cost-efficient option while mitigating risks associated with diesel reliance. The SMART method was employed to weight operational, technical, and financial attributes, validated by SWOT analysis and Kepner-Tregoe risk assessment. Data included primary inputs from focus group discussions (FGDs) and field observations, alongside secondary financial and technical metrics. DT EVs emerged as the optimal choice, offering annual savings of IDR 480 billion versus an infrastructure investment of IDR 183 billion. Sensitivity analysis confirmed robustness, with SWOT highlighting alignment with sustainability goals. Risks, such as charging downtime, were mitigated via phased PDCA implementation. The study provides a replicable framework for mining firms transitioning to electrification, emphasizing cost efficiency and strategic risk management. Future research should explore environmental impacts and co-investment models to enhance ROI.